RESEARCH ON THE ENERGY EFFICIENCY OF HIGH-POWER SYNCHRONOUS MOTORS - Sharobiddinov Saydullo O’ktamjon o`g`li; Makhammadjonov Abdujabbor (Лучшие интеллектуальные исследования, 2024)
A synchronous generator is a special device that can convert any energy into electricity. Such devices are mobile stations, thermal or solar batteries and special equipment [1-2]. Depending on the type of generator, shipping from it, so what device is worth the help. Creation history At the beginning of the 19th century, the Robert Bosch company first developed something similar to a generator. The device was powered by an engine. The tests revealed that the car was not suitable for fast driving, but the developers were able to improve the hardware.